Prediction on the light-assisted exfoliation of multilayered arsenene by the photo-isomerization of azobenzene. Issue 21 (23rd May 2017) - Zhao, Jun; Liu, Chunyan; Guo, Wanlin; Ma, Jing
Abstract : The photo-induced conformational change during the isomerization of azobenzene-based photochromes might be used to promote the exfoliation of multilayered arsenene into single- or few-layered arsenene. Abstract : The exfoliation of gray arsenic into single- or few-layered arsenene is a challenge of utmost importance. We propose here that the conformational change in the photo-isomerization of azobenzene-based photochromes might be used to promote the exfoliation of multilayered arsenene. Our density functional theory calculations show that the trans -to- cis conformational change can lead to an increase of the adjacent interlayer distance of arsenene from 6.59 Å to 11.07 Å. Starting from the transition state, the azobenzene molecule can be isomerized into the more stable trans form based on further ab initio molecular dynamics simulations. Reactive molecular dynamics simulations also show that about a 5 Å interlayer distance change can be induced by the cis -to- trans photo-isomerization of an azobenzene-OC10 H21 molecule. The computational results may inspire the experimental enthusiasm for light-driven synthesis of single or few-layered arsenene.